Clinical analysis and medium-term follow-up of simultaneous interventional therapy for compound congenital heart disease in children: a single-center retrospective study - Ran, Tingting; Feng, Lingxin; Li, Mi; Yi, Qijian; Zhu, Xu; Ji, Xiaojuan (Frontiers in Pediatrics, 2023)
OBJECTIVE: This study aimed to explore the safety and efficacy of simultaneous interventional therapy for compound congenital heart disease (CCHD) in children. METHODS: In total, 155 children with CCHD who received simultaneous interventional therapy according to guidelines and clinical experience were included in Children’s Hospital of Chongqing Medical University between January 2007 and December 2021. Data on clinical manifestations, transthoracic echocardiography, electrocardiogram, and follow-up of the children were retrospectively analyzed. RESULTS: The most common type of CCHD was atrial septal defect (ASD) combined with ventricular septal defect (VSD), accounting for 32.3% of the patients. Simultaneous interventional therapy was successfully administered to 152 children (98.1%). The pulmonary gradient of patients with pulmonary stenosis decreased from 47.3±21.9 mmHg to 15.2±12.2 mmHg (P<0.05) immediately after the procedure. One patient had restenosis 1 month after percutaneous balloon pulmonary valvuloplasty. The right ventricular dimension and left ventricular end-diastolic dimension significantly decreased in the first month after the procedure in patients with ASD combined with VSD. Twenty-five (16.1%) patients had mild residual shunt, which spontaneously disappeared in more than half of these patients 6 months after the procedure. The major adverse events were minimal (n=4, 2.58%), including one patient requiring drug treatment for complete atrioventricular block and three patients receiving surgical treatment because of cardiac erosion, anterior tricuspid valve chordae rupture, and hemolysis. CONCLUSIONS: ASD combined with VSD is the most common type of CCHD in children, and simultaneous interventional therapy for CCHD in children is safe and effective with satisfactory results. Ventricular remodeling can be reversed in patients with ASD combined with VSD 1 month after the procedure. Most adverse events associated with interventional therapy are mild and manageable. Keywords: compound congenital heart disease; pediatric; interventional therapy; transthoracic echocardiography